2014
DOI: 10.5380/abpr.v43i0.38097
|View full text |Cite
|
Sign up to set email alerts
|

<htm>Arthropods associated with the carnivorous plant Drosera latifolia (Droseraceae) in an area of Atlantic Forest (southeastern Brazil)</htm>

Abstract: <htm>Arthropods associated with the carnivorous plant Drosera latifolia (Droseraceae) in an area of Atlantic Forest (southeastern Brazil)</htm>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Arachnopus consisted almost exclusively of flying insects (>99% of all identifiable captured prey), with the only ground‐inhabiting prey groups being Araneae (spiders, 0.36%) and Formicidae (ants, 0.28%; Table 2). This observed dominance of flying insects in the prey spectrum is in line with previous studies investigating the prey spectra of Drosera species producing erect leaves (Achterberg 1973, Thum 1986, Verbeek and Boasson 1993, Costa et al 2014). Furthermore, Diptera (especially Small Nematocera) comprised the highest percentage of identifiable captured prey in all eight studied Drosera species (Table 2), again similar to the results of these previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Arachnopus consisted almost exclusively of flying insects (>99% of all identifiable captured prey), with the only ground‐inhabiting prey groups being Araneae (spiders, 0.36%) and Formicidae (ants, 0.28%; Table 2). This observed dominance of flying insects in the prey spectrum is in line with previous studies investigating the prey spectra of Drosera species producing erect leaves (Achterberg 1973, Thum 1986, Verbeek and Boasson 1993, Costa et al 2014). Furthermore, Diptera (especially Small Nematocera) comprised the highest percentage of identifiable captured prey in all eight studied Drosera species (Table 2), again similar to the results of these previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Arachnopus (34%; Table 2). These soft‐bodied insects are quickly digested by Drosera mucilage (see also Costa et al 2014), and most of the Small Nematocera that could be identified in this study had clearly been freshly captured (indeed, some were still alive at the time of examination). Given that Small Nematocera were the most abundant prey group and the strongest contributor to dissimilarity among most sympatric species (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Arachnopus are characterised by a large, erect growth habit and thread-like aerial leaves which usually do not contact the ground 8 , 32 , thereby excluding most ground-dwelling arthropods as prey. This result is also similar to other prey spectra studies of erect-leaved Drosera from different geographic areas, where flying insects (particularly Diptera) unanimously comprised almost the entire recorded prey 5 , 11 , 44 . Furthermore, this study confirmed the result of Krueger et al 8 that Hemiptera—and within this order especially the Cicadellidae—are exceptionally common in the prey spectra of D. sect.…”
Section: Discussionsupporting
confidence: 90%
“…Results indicate that DNA metabarcoding allows for reliable analysis of prey spectra composition in carnivorous plants at a taxonomic resolution and level of completeness unachievable by traditional morphology-based approaches (as performed, for example, by 4 7 , 9 11 ). Even in remote tropical northern Western Australia, where many (if not most) arthropod species have not yet been accessioned into the BOLD or GenBank barcode reference libraries, this method identified over 90% of obtained OTUs from our sample set; most of them at family-level, but 41% to genus-level, and 17% even down to species rank (Supplementary Data S1 ).…”
Section: Discussionmentioning
confidence: 98%
“…Larvae of Toxomerus basalis likely feed on any available insect prey captured by the sundew leaves, although the majority of the Drosera prey spectrum identified thus far from the few Brazilian species studied consists mostly of small to medium sized adult midges, mosquitos and gnats [ 61 , 97 ]. It is therefore likely that the larval diet of T .…”
Section: Discussionmentioning
confidence: 99%